Non-canonical interactions of the β subunit of the translation elongation complex eEF1B and analysis of their possible functional role - Kapustian, L.M.; Dadlez, M.; Negrutskii, B.S. (Вiopolymers and Cell, 2016)
Aim. To predict protein networks which may comprise the β subunit of the translation elongation complex eEF1B in lung carcinoma cell line. Methods. The protein partners of eEF1Bβ from cytoplasmic extract of A549 cells were identified by co-immunoprecipitation (co-IP) combined with liquid chromatography-tandem mass spectrometry (LC-MS/MS). The molecular interaction network for eEF1Bβ was predicted and visualized by a Cytoscape 3.2.0 program using an MCODE plugin. GO analysis of cellular distribution was performed by a STRAP Program. Results. 162 high-scored proteins interacting with eEF1Bβ in the cytoplasm of lung carcinoma cells A549 have been identified by mass-spectrometry. Possible functional networks involving these contacts were predicted bioinformatically. Conclusions. Four protein networks are identified as possible targets of eEF1Bβ in lung cancer cells. These groups are involved in the cell cycle regulation; DNA replication and repair; chromatin remodeling; chaperoning and signal transduction. The dataallow to narrow down further search for non-canonical cancer-related function of eEF1Bβ. Мета. Передбачити, до яких функціональних кластерів білків клітин карциноми легені А-549 може входити субодиниця β комплексу факторів елонгації трансляції eEF1B. Методи. Білки-партнери eEF1Bβ, отримані з цитоплазматичного екстракту клітин А549 методом ко-імунопреципітації (co-IP), були ідентифіковані за допомогою высокоефективної рідинної хроматографії з тандемною мас-спектрометрією (LC-MS/MS). Сітка молекулярних взаємодій eEF1Bβ була передбачена і побудована за допомогою програми Cytoscape 3.2.0 з використанням плагіна MCODE. Результати. Методом мас-спектрометрії було ідентифіковано 162 білка, що взаємодіють з eEF1Bβ в цитоплазмі клітин карциноми легені A549. Можливі функціональні сітки, що включають ці контакти, були передбачені біоінформатично. Висновки. Чотири білкові сітки були ідентифіковані як можливі мішені eEF1Bβ при раку. Ці групи білків залучені в регуляцію клітинного циклу; реплікацію та репарацію ДНК, ремоделювання хроматину; шаперонну функцію та сигнальну трансдукцію. Отриманні данні дозволяють звузити поле подальшого пошуку неканонічних, пов’язаних з раком функцій eEF1Bβ. Цель. Предсказать функциональные кластеры белков, в какие может быть вовлечена β субъединица комплекса факторов элонгации трансляции eEF1B в клетках карциномы легкого А549. Методы. Белки-партнёры eEF1Bβ, полученные из цитоплазматического экстракта клеток А549 методом ко-иммунопреципитации (co-IP), были идентифицированы с помощью высокоэффективной жидкостной хроматографии и последующей тандемной масс-спектрометрии (LC-MS/MS). Сеть молекулярных взаимодействий eEF1Bβ была предсказана и построена с помощью программы Cytoscape 3.2.0 с использованием плагина MCODE. Результаты. Методом масс-спектрометрии было идентифицировано 162 белка, взаимодействующих с eEF1Bβ в цитоплазме клеток карциномы лёгкого A549. Возможные функциональные сети, включающие эти контакты, были предсказаны биоинфор-матически. Выводы. Четыре белковые сети были идентифицированы в качестве возможных мишеней eEF1Bβ при раке. Эти группы белков вовлечены в регуляцию клеточного цикла; репликацию и реперацию ДНК, ремоделирование хроматина; шаперонную функцию и сигнальную трансдукцию. Полученные данные позволяют сузить поле дальнейшего поиска неканонических, связанных с раком функций eEF1Bβ.